Diffuse large B-cell lymphoma presenting with extensive cutaneous infiltration. - Shamsudin, Norashikin; Chang, Choong Chor (Singapore Medical Association, 2012)
We report a case of systemic diffuse large B-cell lymphoma presenting with extensive infiltration of the skin. A 56-year-old woman presented with a two-month history of pruritic erythematous plaques and nodules over the neck, trunk and upper limbs. She also had night sweats, weight loss, lethargy and reduced effort tolerance. Systemic examination revealed a pale, ill appearance with hepatosplenomegaly and lymphadenopathy. Blood investigations showed pancytopenia (haemoglobin 6.3 g/dL, total white cell count 3.0 × 109/L, platelet count 138 × 109/L) with a few suspicious mononuclear cells and a mildly elevated lactate dehydrogenase level (478 U/L). Skin biopsy demonstrated diffuse sheets and nodular infiltrates of CD20 and CD79a positive neoplastic cells in the dermis and subcutis. Computed tomography revealed multiple cervical, axillary, mediastinal, para-aortic and mesenteric lymph nodes. Bone marrow aspiration and trephine biopsy confirmed marrow involvement by non-Hodgkin's lymphoma. The patient was treated with chemotherapy, which resulted in resolution of the skin lesions.